براہوئی نثری ادب ٹی ناول نا ردوم: Evolution of Brahui Novel - Shahida BiBi (Al-Burz, 2019)
The study of this article is to examine the role of Novel in Brahui society. Brahui literature as compare to other literature in Pakistan has long history which was transferred to a nation to other nation. Which is being called folk literature. But when we take a look towards the progress in the field of Novel writing in Brahui it became much popular as other fields in literature. The first Novel which had been first ever written in Brahui was "Dreehav" authored by Gul Bangulzai. But later Novel writing took place in Brahui literature. the work which is a piece of shadow on Brahui Novel and to elaborate the history of Brahui Novel.